2021
DOI: 10.6023/cjoc202107023
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of 1,3,5-Triazinanes in the Synthesis of Nitrogen-Containing Heterocycles

Abstract: 1,3,5-Triazinanes are an important class of synthons, which could be regarded as the equivalent of formaldehyde imines in constructing various nitrogen-containing heterocyclic skeletons. In recent years, 1,3,5-triazinanes have attracted much attention in the construction of nitrogen-containing heterocyclic compounds. Based on this, the participation of 1,3,5-triazinanes as diatomic, triatomic and four-atom synthons in [2+n], [3+n], [4+n] cycloaddition reactions to construct nitrogen-containing heterocyclic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Second, the types of 1,n-dipoles for the cycloaddition with diazo metal-carbenes are quite limited. Of special interest to the current study, Sun and co-workers discovered that 1,3,5-triazinanes could be used as 1,4-dipole precursors in the gold-catalyzed formal [4 + 1]/[4 + 3] cycloadditions with diazo compounds to produce five-/seven-membered N-heterocycles, in which the catalytically generated diazo gold-carbenes/gold-enolcarbenes reacted as 1,1-/1,3-dipolar adducts (Scheme a) . Also, a recent report showed that imidazolidines were potent 1,5-dipoles and participated well in the rhodium-catalyzed formal [5 + 1]/[5 + 3] cycloadditions with N-sulfonyl 1,2,3-triazoles, wherein the in situ generated α-imino rhodium-carbenes worked as 1,1-/1,3-dipolar species, to afford regiodivergent N-heterocycles, pyrazino-indolines and triazocines (Scheme b) …”
mentioning
confidence: 85%
“…Second, the types of 1,n-dipoles for the cycloaddition with diazo metal-carbenes are quite limited. Of special interest to the current study, Sun and co-workers discovered that 1,3,5-triazinanes could be used as 1,4-dipole precursors in the gold-catalyzed formal [4 + 1]/[4 + 3] cycloadditions with diazo compounds to produce five-/seven-membered N-heterocycles, in which the catalytically generated diazo gold-carbenes/gold-enolcarbenes reacted as 1,1-/1,3-dipolar adducts (Scheme a) . Also, a recent report showed that imidazolidines were potent 1,5-dipoles and participated well in the rhodium-catalyzed formal [5 + 1]/[5 + 3] cycloadditions with N-sulfonyl 1,2,3-triazoles, wherein the in situ generated α-imino rhodium-carbenes worked as 1,1-/1,3-dipolar species, to afford regiodivergent N-heterocycles, pyrazino-indolines and triazocines (Scheme b) …”
mentioning
confidence: 85%
“…In recent years, 1,3,5-triazinanes 18 have attracted much attention and could act as diaza-four-atom synthons to participate in (4+n) cycloadditions for the rapid construction of various nitrogen-containing heterocycles. 19 In 2017, Werz and co-workers developed a (3+4) annulation of DACs with 1,3,5triazinanes 21, leading to 1,3-diazepane products 22 (Scheme 10).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Besides (hetero-)-1,3-dienes, several other four-atom synthons could also react with DACs via (3+4) annulations, including 1,3,5-triazinanes, 15 4-alkenyl indoles 16 and 4alkynyl indoles. 17 In recent years, 1,3,5-triazinanes 18 have attracted much attention and can act as diaza four-atom synthons in (4+n) cycloadditions for the rapid construction of various nitrogen-containing heterocycles. 19 In 2017, Werz and co-workers developed a (3+4) annulation of DACs with 1,3,5-triazinanes 21, leading to 1,3-diazepane products 22 (Scheme 10).…”
Section: Short Review Synthesismentioning
confidence: 99%
“…1,3,5-Triazinanes are stable and readily available synthons, which have been extensively used as formal 1,n-dipoles in the rapid assembly of biologically important heterocycles. 9 Herein, we conceived that 1,3,5-triazinanes might be ideal candidates to react with α-ketoacylsilanes to achieve a novel and unprecedented tandem annulation sequence under mild reaction conditions. Additionally, the construction of a range of privileged scaffolds would represent key structural motifs in terms of unique applications in organic transformation and medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%